Kajian pH Klorofil Terhadap Ikatan Kimia Dye pada TiO2 sebagai Aplikasi Dye-Sensitized Solar Cell (DSSC) - Aziza Hfii Ahliha; Fahru Nurosyid; Agus Supriyanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2018)
This study was conducted to examine the effect of pH on chemical bonding of chlorophyll dye on TiO2 for application of DSSC. Variations of pH used in this study without the addition of buffers, acids, neutrals, and bases. The absorbance of chlorophyll dye and TiO2 were characterized using UV-Vis spectrophotometer. The chemical bonds contained in TiO2-chlorophyll dye were characterized FTIR spectrophotometer. The efficiency of DSSC was calculated using I-V meter. The characterization results showed that pH of acids has the highest absorbance in the wavelength range 400-480 nm and 600-680 nm. The highest conversion efficiency of 0.013% with the transmittance of 89.3% at the wave number 3417 cm-1.